Evaluation of microRNAs as liquid biopsy markers in adrenocortical tumors - Mytareli, Chrysoula; Kalotychou, Vassiliki; Lafioniatis, Alexandros; Kaltsas, Gregory; Zografos, George N.; Markou, Athina; Papanastasiou, Labrini; Fountas, Athanasios; Vasilliadi, Dimitra Argyro; Kassi, Evanthia; Mantzourani, Marina; Angelousi, Anna (Frontiers in Endocrinology, 2025)
IntroductionAdrenal tumors (ATs) encompass a wide differential diagnosis, necessitating a multi-step process for accurate identification. Liquid biopsy emerges as a promising non-invasive technique for distinguishing between malignant and benign, as well as hyperfunctioning and non-functioning cases. Recent studies have highlighted the potential of microRNAs as circulating biomarkers; however, their clinical utility remains underexplored. This study aims to validate the diagnostic performance of selected circulating microRNAs, (miR-483-5p, miR-210, miR-335 and miR-22-3p), identified through microRNA profiling studies, as markers of malignancy or cortisol hypersecretion in a cohort of patients with ATs.MethodsWe collected serum samples from 75 patients with ATs, including 50 cases of adrenocortical adenomas (ACA) and 25 cases of adrenocortical carcinomas (ACC), along with 15 controls. In the ACC subgroup, 16 samples were obtained preoperatively or upon detection of recurrence (active ACC group), while the remaining from disease-free patients with long-term follow-up. Among the 56 patients with ATs evaluated preoperatively (50 with ACAs and 6 with ACC), 26 had non-functioning tumors, 22 exhibited mild autonomous cortisol secretion, and 8 had Cushing syndrome. Quantitative real-time polymerase chain reaction was employed to analyze microRNA expression.ResultsCirculating levels of miR-483-5p and miR-210 were significantly elevated in patients with active ACC compared to both ACAs (p<0.001 and p=0.004, respectively) and controls (p=0.02 and p = 0.03, respectively). Notably, miR-483-5p serum levels were higher in patients with active ACC compared to disease-free ACC patients (p = 0.01). MiR-483-5p demonstrated the best diagnostic accuracy for distinguishing active ACC cases from ACAs, achieving a sensitivity of 81.3% and a specificity of 88%, and from disease-free ACC patients, reaching sensitivity of 81.3% and specificity of 89%. MiR-22-3p serum levels successfully differentiated patients with Cushing syndrome from those with non-functioning ATs (area under the curve=AUC=0.800, 95% CI: 0.653–0.953, p=0.01) and controls (AUC= 0.800, 95% CI: 0.610–0.990, p=0.02). Additionally, circulating miR-22-3p levels exhibited a significant correlation with traditional diagnostic tests for hypercortisolism.ConclusionThis study supports the potential of a liquid biopsy approach as an innovative method for diagnosing and monitoring patients with ATs, offering a complementary tool to existing diagnostic methods.